A smart transformer-rectifier unit for the more electric aircraft - Buticchi, Giampaolo; Gerada, Chris; Ko, Young Jong; Liserre, Marco (2018)
In the framework of the More Electric Aircraft (MEA), an efficient and flexible power distribution system is of paramount importance. Considering the presence of both AC and DC loads at multiple voltage levels, the distribution system of the most modern aircrafts is intrinsically hybrid. In this scenario, the different buses are connected by AC/DC converters. The simplest approach is to use a Transformer-Rectifier Unit (TRU) based on a low-frequency transformer followed by passive rectifiers to perform the AC/DC conversion. This solution, however, is intrinsically uni-directional, introduces current harmonics in the AC side and can have a considerable size. This paper proposes the use of a Smart-TRU, based on a Cascaded H-Bridge topology and a multi-port DC/DC converter, to solve the issues of the traditional TRU, increasing the controllability of the system. Experiments show how the proposed STRU is resilient to faults in the AC side.